2009
DOI: 10.1177/1750481309102452
|View full text |Cite
|
Sign up to set email alerts
|

Coherence in political computer-mediated communication: analyzing topic relevance and drift in chat

Abstract: There is a general perception that synchronous, online chat about politics is fragmented, incoherent, and rife with ad hominem attacks because of its channel characteristics. This study aims to better understand the relative impact of channel of communication versus topic of communication by comparing chat about four different topics. Discourse analysis and coding for topic drift were applied to two hours of chat devoted to the topics of politics, auto racing, entertainment, and cancer support. Findings demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 19 publications
0
16
1
3
Order By: Relevance
“…Janssen and Kies (, p. 321) stress that real‐time discussions like chat rooms, as synchronous discussion spaces, are more likely to provide small talk and jokes, while asynchronous discussion spaces that have no time constraints, like forums, are more apt to provide rational‐critical debate; for an alternative definition of synchronicity, see Jucker and Dürscheid (). These claims are supported by Stromer‐Galley and Martinson (), who found that synchronous online chats are problematic for creating quality discourse. They conclude that short messages lead to underdeveloped arguments, display a lack of coherence, and show a high level of personal attack (Stromer‐Galley & Martinson, , p. 197).…”
Section: Previous Researchmentioning
confidence: 83%
See 2 more Smart Citations
“…Janssen and Kies (, p. 321) stress that real‐time discussions like chat rooms, as synchronous discussion spaces, are more likely to provide small talk and jokes, while asynchronous discussion spaces that have no time constraints, like forums, are more apt to provide rational‐critical debate; for an alternative definition of synchronicity, see Jucker and Dürscheid (). These claims are supported by Stromer‐Galley and Martinson (), who found that synchronous online chats are problematic for creating quality discourse. They conclude that short messages lead to underdeveloped arguments, display a lack of coherence, and show a high level of personal attack (Stromer‐Galley & Martinson, , p. 197).…”
Section: Previous Researchmentioning
confidence: 83%
“…These claims are supported by Stromer‐Galley and Martinson (), who found that synchronous online chats are problematic for creating quality discourse. They conclude that short messages lead to underdeveloped arguments, display a lack of coherence, and show a high level of personal attack (Stromer‐Galley & Martinson, , p. 197). Strandberg and Berg () provide evidence from an online experiment that suggests that asynchronous discussion is a crucial design factor for online deliberation.…”
Section: Previous Researchmentioning
confidence: 83%
See 1 more Smart Citation
“…In particular, several researchers have noted that group chat conversations can have problems with coherence, in part due to the inability to precisely time when messages arrive in the chat room (Herring, 1999;Markman, 2013;Stromer-Galley & Martinson, 2009). argued that many of the coherence issues associated with multi-party chat may be mitigated in IM by the reduced number of participants, and thus this medium is worthy of additional study.…”
Section: Instant Messaging As Conversationmentioning
confidence: 99%
“…Researchers have investigated informal political talk in a variety of online forums, which include (Usenet) newsgroups (Davis, 2005;Hill & Hughes, 1998;Papacharissi, 2004;Schneider, 1997;Wilhelm, 1999;Zhang, Cao, & Tran, 2013); news media sponsored forums -newspapers (Graham, 2010b;Schutz, 2000;Strandberg, 2008;Tanner, 2001;Tsaliki, 2002); forums hosted by political parties and governments -excluding e-consultations (Dunne, 2009;Graham & Witschge, 2003;Hagemann, 2002;Jankowski & Van Os, 2004;Winkler, 2005); online deliberative initiatives (Dahlberg, 2001b); comparisons between different types (Brants, 2002;Graham, 2011;Jensen, 2003); third spaces -non-political forums (Graham, , 2010a(Graham, , 2012a; other platforms such as chat (Stromer-Galley & Martinson, 2009), blogs (Koop & Jansen, 2009) and readers' comments (Graham, 2012b;Ruiz, Domingo, Micó, & Díaz-Noci, 2011); and social media network sites such as Facebook and YouTube (Halpern & Gibbs, 2013;Robertson, Vatrapu, & Medina, 2010). 4 Studies here focus on measuring the deliberativeness of political talk as a means of determining the extent to which the Internet is conducive to (particular) conditions of deliberation.…”
Section: Analysing and Assessing Online Political Talkmentioning
confidence: 99%